ESAF at ten years : economic adjustment and reform in low-income countries (IMF WashingtonUS, 1997)
Supplies a summary of the latest periodic review of experience under the Structural Adjustment Facility (SAF)- and Enhanced Structural Adjustment Facility (ESAF)-supported programs. Provides an overview of policies and economic developments in 36 countries during 1986-95, pulls together the main lessons from this experience, and sets out proposals for strengthening the design and implementation of future programs.
DC